Analytical study of training program factors to develop the competency of regional operating officer (ROO) in the virtual service provider office (VSPO) in Thailand - Phongpisanu Boonda; Aree Preedeekul; Phataraphon Markmee (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - Virtual regional service provider is a key management mechanism created to realize the health service system development plans and a mechanism established to bring about integration of all elements of the health system. However, a virtual service provider office (VSPO) to support the work of the executive has not yet been formally established, and there are no operations practitioners deployed yet, who are necessary to develop the competency of regional operating officer (ROO) in each province. The purpose of this paper is to analyze training program factors to develop the competency of ROO in the VSPO in Thailand. Design/methodology/approach - This is a descriptive research that used structural equation model. The research sample consisted of 274 executives and 664 practitioners in the Vice Chief of the provincial health office under the 12 regions; executives' questionnaire and a VSPO questionnaire were used as tools for this study; data were statistically analyzed by three methods, namely, exploratory factor analysis (EFA), second-order confirmatory factor analysis (second-order CFA), and path analysis (PA). Findings - The variable model was composed of ten factors, selected from 40 variables, which are as follows: service plan and personal administration, summary to present for administrators in the VSPO, network management and team building, summary to adjust strategies, key performance indicator (KPI) and action plan, new management skills, system thinking, analytical thinking, synthesis thinking, conflict management style, and leadership; presentation of methods and data for monitoring, presentation skill, conference management skill; researching, learning skill, communication skill exercise, action plan workshop, preparation to study in the fields workshop; fiscal and monetary, internal control and risk management; project management, monitoring, and data definition; and positive thinking, conflict management process, negotiation skill contingency management. Originality/value - Ten factors of the variable model of training program factors to develop the competency of ROO in the VSPO in Thailand had high construct validity and they were analyzed using three methods, i.e. EFA, second-order CFA and PA, that were appropriate to be used for developing a training program.